Managing banking risks - Cade, Eddie (Gresham Books, in association with the Chartered Institute of Bankers, 1997)
This book fills a gap in banking literature by providing a professional and sophisticated 'risk' primer for bank directors, executives and staff at every level as well as students, analysts and commentators on the banking scene. The breadth of focus is exceptional in covering the full range of banking risks, rather than the customary specialist segment. The book begins by defining risk itself and discussing how it can be approached in a banking context. It goes on to examine the concepts of volatility, expected and unexpected loss, the role of risk capital, rate of return and the required reward for risk (the 'cost of capital'). The author identifies five generic types of primary banking risk and one universal secondary type. Each of these is explored in turn from solvency and liquidity risks to credit risk, interest rate risk, price risks and operating risks. This treatment gives the reader an insight into modern risk management and hedging techniques, and many other relevant topics. Legal and regulatory issues and constraints are considered within an international frame of reference. The book offers practical guidance on the role of a bank's board and executive management, organisation and co-ordination of risk management.